EFFECT OF SUB MAXIMAL EXERCISE ON ENDOTHELIUM-DERIVED NITRIC OXIDE CONCENTRATIONS IN HEALTHY YOUNG SUBJECTS. - mukherjee, kasturi; biswas, Soumika; Banerjee, Sayari; Bhattacharyya, Raghunath (Journal of Drug Delivery and Therapeutics, 2014)
Objective: To determine any possible contribution of 10 minutes single session sub maximal exercise on Nitric oxide level in healthy young population. Design: A descriptive observational study on forty healthy volunteers (20 male & 20 female) of 20-30 years designed to evaluate the level of nitric oxide after 10 minutes cycling. Intervention:Â Young populations are allowed to exercise in a bicycle ergo meter for 10 minutes regular exercise under protocol YMCA Sub maximal Cycle Ergo meter Testing against a constant workload. Â Main outcome measures: Serum Creatine Phosphokinase Â and Â Nitrate-Nitrite ratio (Surrogate marker of nitric oxide)Â measured. Continuous heart rate monitoring is done from ECG system. Vo2 max calculated and energy expenditure for physical activity obtained from prediction equation after adjusting age, gender & body mass. Results: Comparison of Activity Energy Expenditure (AEE) before and after exercise done, (p value<0.0001)(n = 40). Â Significant amount of Â work done in this exercise. Increase in the serum creatine phosphokinase level (p value<0.0001). Serum Nitrate-Nitrite ratio (nitric oxide level) showed increase (p value 0.1113) in post exercise level. Conclusion: As far as energy expenditure concerned, significant muscular activity in both male & female showed insignificant endothelium derived Nitric oxide production. On the basis of the data obtained it is evident that in a single session sub maximal exercise beneficial effect of vasodilator Nitric oxide was not observed in studiedÂ young population. Keywords: sub maximal exercise, activity energy expenditure, nitrate-nitrite ratio.